Adminstrative Analysis of Woman Representation in Public Sector: A Case of Kabupaten Kediri, East Java - Kuntariningsih, Apri; Negoro, Aria Adi (Universitas Pancasakti Tegal, 2023)
Women play an important role in development, both in developing countries and in developed countries. As mentioned in Law No. 22/1999 and No. 23/2014, women should have an equal role in local government. This study aims to analyze the law's implementation in terms of women's role in local government in the Kediri Regency, East Java. This study showed that females dominated the number of government employees. The proportion of women working in public services varies across the office services. Women are concentrated in specific sectors requiring expertise, such as health care, education and social welfare. Conversely, the lowest proportion of women is in construction-related sectors. However, the proportion of women in the House of Representatives remained low. These findings imply that local governments should pay attention to allocating female employees. Regencies with female (or male) employee disproportion should be transferred reasonably, the mutation of employees should be fair, and the recruitment of new employees should also be proportionate.